Qur'anic Logic in The Story of Prophets Abraham And Moses - Taqiyuddin, Muhammad (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
This research intends to reveal the logical side of understanding God, from two great Prophets, Ibrahim and Musa through their stories in the Qur'an. This is because one of the elements of the Qur'anic mu'jizat, is a logical narrative that often appears in the dialogue of the prophets. Prophet Ibrahim and Prophet Musa, were sent to a people who were smart enough to argue regarding their own misguidance. Both faced similar problems: facing idolaters and unjust rulers. In terms of requests to Allah, both even asked for almost the same thing: Prophet Ibrahim asked his descendants to be granted prophethood. Prophet Musa, asked that his brother be appointed Prophet. Both of them, at the level of trying to understand the Power of God itself: Prophet Ibrahim asked God about bringing the dead back to life; Prophet Moses asked about the knowledge that Prophet Khidir possessed. Methodically, this article is a literature study with a narrative approach to the same theme found in the stories of Prophet Ibrahim and Prophet Moses. This study concludes that there are at least two things in which both logically refute idolaters and rulers through narratives that are neatly recorded in the Qur'an. It also logically shows human aspects of kinship and curiosity. Contribution: This research reveals the logical approach in the Qur'anic narrative through the stories of Prophet Ibrahim and Prophet Musa in understanding divinity.